Cell Cycle Analysis of Hematopoietic Stem and Progenitor Cells by Multicolor Flow Cytometry. Issue 1 (18th October 2018) - Galvin, Amy; Weglarz, Meredith; Folz‐Donahue, Kat; Handley, Maris; Baum, Misa; Mazzola, Michael; Litwa, Hannah; Scadden, David T.; Silberstein, Lev
Abstract: Maintenance of hematopoietic stem cell (HSC) quiescence is critical for self‐renewal and differentiation into mature lineages. Therefore, the ability to reliably detect abnormal HSC cycling is essential for experiments that seek to investigate abnormalities of HSC function. The ability to reproducibly evaluate cell cycle status in a rare cell subset requires careful optimization of multiple parameters during cell preparation and sample processing. Here, we describe a method where data acquisition parameters and fluorochrome combination for long‐term HSC staining have been specifically designed for concurrent use with DAPI and Ki‐67 antibodies. © 2018 by John Wiley & Sons, Inc.